Gastroesophageal Reflux After Sleeve Gastrectomy - Guzman-Pruneda, Francisco A.; Brethauer, Stacy A. (Journal of gastrointestinal surgery, 2021)
Sleeve gastrectomy continues to be the most commonly performed bariatric operation worldwide. Development or worsening of pre-existing GERD has been recognized as a significant issue postoperatively. There is a paucity of information concerning the most appropriate preoperative workup and the technical and anatomical factors that may or may not contribute to the occurrence of reflux symptoms. Contemporary data quality is deficient given the predominantly retrospective nature, limited follow-up time, and heterogeneous outcome measures across studies. This has produced mixed results regarding the postoperative incidence and severity of GERD. Ultimately, better-constructed investigations are needed in order to offer evidence-based recommendations that may guide preoperative workup and improved patient selection criteria.